2012
DOI: 10.1371/journal.pone.0051266
|View full text |Cite
|
Sign up to set email alerts
|

Global Profiling of Alternative Splicing Events and Gene Expression Regulated by hnRNPH/F

Abstract: In this study, we have investigated the global impact of heterogeneous nuclear Ribonuclear Protein (hnRNP) H/F-mediated regulation of splicing events and gene expression in oligodendrocytes. We have performed a genome-wide transcriptomic analysis at the gene and exon levels in Oli-neu cells treated with siRNA that targets hnRNPH/F compared to untreated cells using Affymetrix Exon Array. Gene expression levels and regulated exons were identified with the GenoSplice EASANA algorithm. Bioinformatics analyses were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 42 publications
3
61
0
Order By: Relevance
“…In general binding of hnRNP H1 to intronic regions particularly in the region downstream of the 5 0 splice site usually results in enhance use of the splice site. 34,35 This is a possible mechanism by which hnRNP H1 increases the inclusion of exon 16 as RNA chromatography demonstrated hnRNP H1 binding to the introns surrounding exon 16 with particularly strong binding to intron 16. Indeed there are predicted binding sites for hnRNP H1 in introns 15 and 16 in the regions covered by H5 and H6 oligonucleotides.…”
Section: Discussionmentioning
confidence: 99%
“…In general binding of hnRNP H1 to intronic regions particularly in the region downstream of the 5 0 splice site usually results in enhance use of the splice site. 34,35 This is a possible mechanism by which hnRNP H1 increases the inclusion of exon 16 as RNA chromatography demonstrated hnRNP H1 binding to the introns surrounding exon 16 with particularly strong binding to intron 16. Indeed there are predicted binding sites for hnRNP H1 in introns 15 and 16 in the regions covered by H5 and H6 oligonucleotides.…”
Section: Discussionmentioning
confidence: 99%
“…The significance of HNRNPH in controlling alternative splicing of neural genes was previously shown in oligodendrocytes. 55,56 Of note, HNRNPH1 regulates alternative splicing of the neuron-specific exon N of REST. 57 The role of HNRNPH on TRF2 splicing in neuronal differentiation was tested in two model systems.…”
Section: Nuclear Role Of Trf2mentioning
confidence: 99%
“…This protein tends to form a heterodimer with hnRNP F and shows preference for G-rich tracts of RNA. 2,[6][7][8] It has also been shown that hnRNP H1 interacts with the DGCR8 complex and facilitates microRNA processing in HeLa cells. 9 The impact of hnRNP H1 binding on alternative splicing has been associated with several diseases, such as cystic fibrosis, 10 congenital myasthemic syndrome, 11 and amyotrophic lateral sclerosis (ALS).…”
Section: Introductionmentioning
confidence: 99%
“…18 In addition to these targeted analyses, genome-wide studies have revealed hnRNP H1s role, in conjunction with hnRNP F, in promoting both exon inclusion and skipping. 8 Other recent studies have linked hnRNP H1 to alternative cleavage and polyadenylation, 6 and established the cooperative roles of the hnRNP proteins in the regulation of splicing. 2 By employing a combined strategy with 4 different high-throughput approaches, we were able to provide a more refined and accurate picture for hnRNP H1 in splicing regulation and extend our understanding of its participation in polyadenylation and mRNA decay.…”
Section: Introductionmentioning
confidence: 99%